2023
DOI: 10.1021/acsami.3c04595
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Subthreshold Swing and Hysteresis in Hf0.5Zr0.5O2-Based MoS2 Negative Capacitance Field-Effect Transistors by Modulating Capacitance Matching

Abstract: Negative capacitance field effect transistors made of Hf0.5Zr0.5O2 (HZO) are one of the most promising candidates for low-power-density devices because of the extremely steep subthreshold swing and high open-state currents resulting from the addition of ferroelectric materials in the gate dielectric layer. In this paper, HZO thin films were prepared by magnetron sputtering combined with rapid thermal annealing. Their ferroelectric properties were adjusted by changing the annealing temperature and the thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Furthermore, Figure c shows the I d - SS scatter plot extracted from Figure b for the pure MoS 2 , AuNPs/MoS 2 , and AuNPs/Al 2 O 3 /MoS 2 phototransistors, with the lowest SS ’s of 69.1, 213.3, and 28.2 mV/dec, respectively. The involved mechanisms for the improved SS of the AuNPs/Al 2 O 3 /MoS 2 device compared to other two devices lie in (1) the enhancement of the ferroelectric polarization of the HZO film by in situ prepared AuNPs and (2) the stabilized NC effect and effectively improved interface qualities by the insertion of the Al 2 O 3 layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Figure c shows the I d - SS scatter plot extracted from Figure b for the pure MoS 2 , AuNPs/MoS 2 , and AuNPs/Al 2 O 3 /MoS 2 phototransistors, with the lowest SS ’s of 69.1, 213.3, and 28.2 mV/dec, respectively. The involved mechanisms for the improved SS of the AuNPs/Al 2 O 3 /MoS 2 device compared to other two devices lie in (1) the enhancement of the ferroelectric polarization of the HZO film by in situ prepared AuNPs and (2) the stabilized NC effect and effectively improved interface qualities by the insertion of the Al 2 O 3 layer.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the tensile strain caused by the AuNPs in MoS 2 narrows its bandgap, facilitating the broadband photodetection. Moreover, Al 2 O 3 as a capacitance-matching layer (CML) for the HZO film can further suppress the I off , reduce the SS , and enhance the detectivity by utilizing NC effect of the HZO film. , For the first time, a NC-LSPR-coupled phototransistor is fabricated, demonstrating a remarkable responsivity ( R ) and a detectivity ( D* ) at 528 nm (122.5 A/W, 3.23 × 10 14 Jones) and 740 nm (28.3 A/W, 9.14 × 10 13 Jones), respectively, i.e., high detectivity and broadband detection are concurrently achieved. Additionally, the good stability and uniformity of the photodetectors with a stack of HZO/AuNPs/Al 2 O 3 /MoS 2 are demonstrated through a statistic analysis of 30 phototransistors.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recently, Guo et al also reported MoS 2 /HZO NC-FE-FET, exhibiting a steep SS of 27.9 mV dec −1 and a high I ON /I OFF ratio of 1.5 × 10 7 . 10 An ultralow SS of 11 mV dec −1 was reported by Daw et al for a NC-Dirac source−drain FET with 2D CuInP 2 S 6 (CIPS) flakes/MoS 2 /graphene structure. 11 Although 2D materials are emerging for next-generation quantum computing and nanoscale integration, oxide semiconductors could be suitable candidates for low-cost and largescale integration (LSI) of energy-efficient high-speed electronics.…”
mentioning
confidence: 87%
“…Note that the steep SS below 60 mV dec −1 could have originated from the NC effect in FE-ZAO TFTs. 3,6,8,10,11 To investigate the needle-like hump phenomena at ultralow V DS during the forward sweep, the I DS −V GS hysteresis characteristics were measured at V DS = 0.1−0.9 mV with 0.2 mV steps, as depicted in Figure 4a. Figure 4b exhibits the zoomed-in view of the needle-like hump for the forward sweep, demonstrating the gradual decrease of hump behavior near V GS = 0 V with increasing V DS .…”
mentioning
confidence: 99%
See 1 more Smart Citation